ANALYSIS OF THE NATURAL RESOURCES CONSERVATION CENTER IN THE MANAGEMENT OF THE DUSUN BALAR LAKE NATURAL RESERVE, BENGKULU CITY - Bayu Mandala Putra; Titi Darmi (Yayasan Wayan Marwan Pulungan, 2023)
This research discusses the analysis of the Natural Resource Conservation Center in managing the Dusun Besar Lake Nature Reserve, Bengkulu City. Although the management area aims to preserve natural resources and the environment, human activities and management issues threaten sustainability. The Bengkulu Province strives to address these problems for fair and sustainable forest management. The research employs a qualitative method focusing on a case study to analyze the planning, organizing, movement, and supervision in the context of Nature Reserve management. The research findings indicate that Bengkulu adheres to government regulations and long-term Dusun Besar Lake Nature Reserve management plans. The study also identifies crucial indicators in planning and organizing the three conservation sections in Bengkulu and the importance of movement and supervision functions in activity implementation.